Pengaruh Inflasi, BI Rate, NPF, dan BOPO terhadap Profitabilitas Bank Umum Syariah di Indonesia - Toufan Aldian Syah (el-Jizya : Jurnal Ekonomi Islam, 2018)
Banking industry has a very important role in economic development in a country. Indonesia, which is the largest Muslim country in the world, certainly has the prospect of the development of Sharia Banking Industry is very good in the future. However, the development of Sharia Bank has been slowing down in recent years and the profitability of sharia comercial banking is still below the ideal value. This study aims to determine the internal factors and external factors that affect the profitability of Sharia Bank in the year of January 2012 until August 2017. The variables used in this study are ROA, Inflation, NPF, and BOPO. The data used is aggregate data of all Sharia Commercial Banks recorded at Bank Indonesia. Measurement of Statistic Description, F-Test, T-Test, Correlation Coefficient, Coefficient of Determination and Multiple Linear Regression using IBM SPSS 21 software. The results showed that significant negative effect of BI rate, NPF and BOPO was found, while Inflation variable showed negative but not significant. Overall, the above variables affect the ROA of 87.7%, while 12.3% is likely to be influenced by other factors.